The viability of implementing dispute board in Malaysia - Makmor, M.; Ismail, Z.; Zulkifly, U.K.; Mohd Rahim, F.A. (2011)
This paper is performed mainly to introduce Dispute Board (DB) as the one of the many Alternative Dispute Resolutions (ADRs) to be applied into the Malaysian construction industry to reduce and minimize the amount of disputes. This research is carried out by interviewing nine respondents which consist of registered Quantity Surveyors. Litigation and arbitration has been widely applied in Malaysia for dispute settlement. Both methods, however, do become more tedious and arduous processes to go through to resolve disputes. Mediation, on the other hand, has been a new alternative for dispute settlement in the Malaysian construction industry. Nevertheless, arbitration and mediation have not yet made a big impact in the numbers of disputes arising in the Malaysian construction industry. Therefore, this paper unveils the viability of implementing Dispute Board as a better and more efficient method of ADR that is determined in the outset of the project. Dispute Board is able to reduce the amount of disputes arising in the Malaysian construction industry.